DETECTION OF THE RESISTANCE OF MYCOBACTERIUM TUBERCULOSIS FROM SPECIMENS WITH TB PATIENTS IN SEMARANG BALKESMAS - Widodo Widodo; Djoko Priyatno (Poltekkes Kemenkes Semarang, 2020)
Detection of the occurrence of resistance of Mycobacterium tuberculosis from sputum specimens of tuberculosis patients in BALKESMAS Semarang, using a non-experimental cross-sectional design with a non-intervention approach survey method, sputum samples of TB patients who did not convert during treatment Percentage of culture results from Nine patients was 33.3%, test DST from sensitive first-line OAT samples, morphological and size changes (1.82 - 1.87 µm), showed that first-line drugs were still effective for treatment in patients who took part in this study.